La carrière criminelle : définition et prédiction - LeBlanc, Marc (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
The concept of a criminal «career» is being used more and more in the recent criminological literature. This article analyzes the pertinence of explaining this concept by its specific components. To do this, the criminal activities of a sample of adolescents and a group of wards of the Montreal Court between the ages of seven and twenty-five are described (precocity, frequency, variety, gravity, aggravation, violence, duration). Two stages were detected in the criminal career, their degree of stability and paths of development. The dynamics of the criminal activity are described. Finally, the predictability of an intensification of criminal activities is analyzed. Given the high degree of stability, predictability and mobility (marked by aggravation of the criminal activity), we conclude that recourse to the concept of a criminal career is essential to a better understanding and more accurate diagnosis of the process of acting out.